Virtual Genfūkei: The Internet as Originary Landscape in Three Born-Digital Literatures - Glassford, Rachel Sharón (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2021)
Digital folklorists and ethnographers have engaged with the advent of the internet age in various ways, but few scholars have approached the internet from the perspective of literary analysis to address its function as a fictional setting. This dissertation addresses that gap by applying literary critic Takeo Okuno's genfūkei (originary landscape) theory to three works of born-digital fiction, all written and set during the early-Post-Internet (the period between the Dot Com Boom and the 2018 repeal of network neutrality regulations in the United States). Genfūkei proposes a fictive-remembered system of nostalgia whereby the personal and collective memories of a work's creators and readership fuse, forming a literary trend that unites portrayals of a particular landscape and presents this setting in a specific way, underpinned by specific ideas (often misconceptions) about a particular time and place in the past. This conceptual framework emphasizes the high degree of interactivity between literary or cinematic text and the public imagination; it is similar to theories of artistic nostalgia put forth by media critics Frederic Jameson, Mark Fisher, and Simon Reynolds, whose writings are here used in recontextualizing Okuno's work in regard to the internet-as-place. A comparative close reading of three born digital literatures reveals common themes, rhetoric, and framing devices possibly indicative of widespread perceptions of the early-Post-Internet period shared by millennial creators. Moreover, the practical application of Okuno's genfūkei concept demonstrates that the originary landscape can appear in a given text as both feature and mode in addition to its uses as an analytical tool; thus, critics are advised to exercise caution when using this terminology in future applications of Okuno's theory. Finally, the results of this study suggest that the early-Post-Internet period has been mythologized as a frontier, using the language and archetypes associated with the frontier myth.
Keywords: Comparative Literature